Pengelolaan Digital Filing sebagai Bentuk Penerapan E-business di PT Dirgantara Indonesia - Fenny Damayanti; Salma Alkindira (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
Nowadays many companies have make use of information technology. Implementation of information technology has been done partly of wholly, depending on each company’s need. Companies are aware of the benefit in making use of information technology to win the competition in business which is tighter and competitive. The decision to make use of information technology should be started by having the blue print so that the implementation of information technology can be sustained and bring a competitive advantage to the company. One of the form of information technology’s implementation in company is known as e-business. Digital filing is one of the form of e-business implementation in company. Most of work done in company is producing or making documents. Digital filing’s role as a part of information technology is important in managing the company’s documents. By having an excellent document management, documents as an important assets for company, could be maintained and easily found when needed. PT Dirgantara Indonesia as one of the well known state-owned company in Indonesia and overseas has implemented the digital filing as a form of e-business implementation. PT Dirgantara Indonesia is aware of the benefit in using the digital filing in keeping and finding documents needed. This study uses descriptive methodology, while data collections are collected through observation, interview, literature and documentation studies. The results show that the decision in implementing digital filing is a right decision that PT Dirgantara Indonesia have taken, which is in line with PT Dirgantara Indonesia’s vision: “To become the world-class company in the industry based on mastering a high technology and being able to compete in the global market by focusing on cost efficiency”. It proves that PT Dirgantara Indonesia aware to change its business processes platform to digital. Documents management done by PT Dirgantara Indonesia consists of 2 (two) main activities they are filing and finding documents needed. PT Dirgantara Indonesia needs to maintain the hardware and software, internet connection so that documents management can be done smoothly. Keywords: E-business, Digital Filing, Document Management, Information Technology